PRAKTIK POLITICAL WILLINGNESS DALAM PENERAPAN AKUNTANSI BERBASIS AKRUAL PADA SEKTOR PUBLIK - Sudarwadi, Hustianto; Parastri, Desirianingsih; Narwawan, Destri (Cakrawala Management Business Journal, 2024)
The research aims to determine the achievement of political willingness practices in implementing accrual-based accounting in the public sector. This research was conducted at the Regional Secretariat of Manokwari Regency. The type research used is qualitative research based on an interpretive paradigm. Data collection in this research was direct interviews with informants. This research data analysis method uses interpretive analysis to test the validity of the data based on data triangulation and theory triangulation. The results of this research indicate that the Regency Manokwari Regional Secretariat has implemented accrual-based accounting in accordance with Government Regulation Number 71 Of 2010 Concerning Accrual-Based Government Accounting Standards. The practices of political willingness has a positive impact on the preparation of government financial reports. The achievement of the practice of political willingness in implementing accrual-based accounting at the Regional Secretariat Of Manokwari Regency is measured by several indicators, namely initiative, priority, mobilization of political support, law enforcement and business sustainability so as to produce quality financial reports that are transparent and accountable.